2005
DOI: 10.1021/ic050892+
|View full text |Cite
|
Sign up to set email alerts
|

Uridine Binding by Zn(II) Macrocyclic Complexes:  Diversion of RNA Cleavage Catalysts

Abstract: Zn(II) complexes of 1-oxa-4,7,10-triazacyclododecane (12[ane]N3O), 1,5,9-triazacyclododecane (12[ane]N3), and 1-hydroxyethyl-1,4,7-triazacyclononane (9[ane]N3OH) promote cleavage of the RNA analogue, 2-hydroxypropyl-4-nitrophenyl phosphate (HpPNP) at pH 8.0, I=0.10 M (NaCl), 25 degrees C with second-order rate constants of 8.9x10(-3), 9.0x10(-3), and 3.3x10(-3) M-1 s-1, respectively. Cleavage of HpPNP by these catalysts is inhibited by uridine with inhibition constants (Ki) of 1.2, 0.46, and 45 mM, respectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
43
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(50 citation statements)
references
References 62 publications
5
43
2
Order By: Relevance
“…We have recently shown that the magnitude of the uridine anion binding constant correlates strongly to the hydroxide binding constant for a series of structurally distinct Zn(II) macrocyclic complexes. This suggests that the Zn(II) anion interaction dominates and that hydrogen bonding is not an important contribution in recognition [19]. Consistent with this correlation, Zn (2) and Zn(3) have similar hydroxide binding constants and similar uridine binding constants.…”
Section: Kinetics Of Hppnp Cleavagesupporting
confidence: 53%
See 3 more Smart Citations
“…We have recently shown that the magnitude of the uridine anion binding constant correlates strongly to the hydroxide binding constant for a series of structurally distinct Zn(II) macrocyclic complexes. This suggests that the Zn(II) anion interaction dominates and that hydrogen bonding is not an important contribution in recognition [19]. Consistent with this correlation, Zn (2) and Zn(3) have similar hydroxide binding constants and similar uridine binding constants.…”
Section: Kinetics Of Hppnp Cleavagesupporting
confidence: 53%
“…A characteristic property of the Zn(3) complex is its tight (millimolar) binding to uridine nucleobases through interaction with the N3 of uridine [19,47]. This interaction competes with binding of the catalyst to the phosphate ester and leads to inhibition of catalysis.…”
Section: Kinetics Of Hppnp Cleavagementioning
confidence: 99%
See 2 more Smart Citations
“…7 Nowadays interest is focused on the synthesis of macrocyclic complexes with potential medicinal applications, as contrast-enhancing agents in magnetic resonance imaging (MRI), 8 as N.M.R shift and relaxation reagents 9 and as RNA cleavage catalyst. 10,11 Macrocyclic complexes of transition metals exhibit antibacterial, 12 anticarcinogenic, 13 antifertility, 14 and antifungal 15 activities.…”
Section: Introductionmentioning
confidence: 99%